Preparation of Hydrophobic Poly (lauryl methacrylate-divinyl benzene) Coated Magnetic Nano-composite Particles and Their Application as Adsorbents for Organic Pollutants (Rajshahi University Journal of Science and Engineering, 2016)
This work introduces a method for the preparation of magnetic nano-composite particles coated with highly crosslinked poly (lauryl methacrylate) (PLMA), a hydrophobic polymer containing long chain alkyl groups for application in waste water treatment. The produced magnetic composite particles named Fe3O4/SiO2/P(LMA-DVB) were characterized by Fourier Transform IR (FTIR), Transmission electron microscopy (TEM) and X-ray diffractometer (XRD) analyses. Then the prepared composite particles were used for the removal of organic pollutants from water. The adsorption behavior was dependent on the nature of the pollutants with congo red showed highest adsorption efficiency.